A distributional survey and habitat model for the endangered northern bettong Bettongia tropica in tropical Queensland - Laurance, William F. (Biological Conservation, 1997)
The northern bettong Bettongia tropica is an endangered rat-kangaroo that occurs only in certain dry and mesic forests in tropical Queensland, Australia. In 1994 and 1995 I conducted a live-trapping survey at 152 sites throughout its potential geographic range. Detailed floristic, physiognomic. topographic and geology data from each site were used to develop a predictive model of bettong habitat requirements, using generalized linear modeling. Data from 62 spotlighting censuses and opportunistic observations were also used to assess potential threats to northern bettongs posed by introduced foxes Vulpes vulpes, while trapping and habitat data were employed to evaluate possible effects of rooting-damage from feral pigs and competition from rufous bettongs Aepyprymnus rufescens on northern bettong populations. The northern bettong was detected in only one area, the Lamb Range, where it was present at nearly half (33/70) of the sites surveyed. Sparse populations recorded previously at several other localities in north Queensland may have declined or disappeared. A multiple Poisson regression model indicated that northern bettongs were strongly associated with certain types of wet and mesic sclerophyll forests and woodlands, while rainforest and rainforest-invaded wet sclerophyll forests were avoided. Northern bettongs occurred only on infertile metamorphic and granitic substrates, and were never detected on richer basaltic or alluvial soils. This probably occurs because fruit-bodies of ectomycorrhizal fungi, which are a key food resource of northern bettongs, are most abundant on infertile soils. Foxes were never detected during the survey, and are unlikely to threaten northern bettong populations at present. Circumstantial evidence suggests that interspecific competition from rufous bettongs is also of minimal importance. Rooting damage by fetal pigs, however, may be more significant; northern bettongs were rarely detected at sites with heavy pig damage, and this may be because pigs are also feeding on fungal fruit-bodies. At present, the greatest threat to northern bettongs is probably encroaching land development, especially in the crucial Lamb Range area. Northern Queensland is experiencing rapid population growth, and local shires are attempting to shunt residential development onto areas with infertile soils to avoid the loss of productive agricultural land. While normally a laudable practice, this is precisely the wrong policy in this specific region. A re-evaluation of the strategic development plans of local shires is urgently needed to protect remaining habitats of the northern bettong, Habitat management, especially regular burning, is also required in key bettong habitats. Burning will prevent further invasion of wet sclerophyll forests by rainforest vegetation, which renders the habitat unsuitable for bettongs, and also is likely to promote the local production of fungal fruit-bodies upon which the northern bettong is highly dependent.
Keywords: Endangered Mammal; Habitat Requirement; Interspecific Competition; Management; Northern Bettong; Residential Development; Australia, Queensland, Lamb Range; Aepyprymnus Rufescens; Bettongia Tropica; Sus Scrofa; Vulpes Vulpes